Analisis Faktor Yang Mempengaruhi Manajemen Pajak Dengan Indikator Effective Tax Rate (ETR) - Joko Susilo; Syarifah Ratih Kartika Sari (Universitas Merdeka Madiun, 2022)
This research aims to analyze the factors that affect tax management to effective tax rate (ETR). The dependent variable used in this research is the effective tax rate. Meanwhile, the independent variables are leverage, profitability, and capital intensity ratio. The population in this research were manufacturing companies in the pharmaceutical sub-sector consumer goods industry which were listed on the Indonesia Stock Exchange (BEI) in period 2016-2019. The sample technique used purposive sampling method and obtained 36 samples for 4 years. Data obtained from secondary data of 9 companies financial statements. Data analysis was performed using multiple linear regression with SPSS version 16.00 for windows. These results indicate that partially the profitability and capital intensity ratio variables have no affect on effective tax rate. Leverage variable affects on effective tax rate. Meanwhile, simultaneously all variables have an affect on the effective tax rate, and the value of Adjusted R Square is 18.6%.